Sweden now 1981-II_2 - Testologen Ltd. (IMU-Testologen AB, 1985)
In the mid-1960s, Testologen AB in collaboration with a group of advertisers, introduced a new way of investigation, where data about the target groups - socio-economic data, interests, purchasing habits, possessions, buying intentions - and data on reading habits were collected in the same survey. At SND there are now surveys available from the Sweden Now series covering a 20-year period, 1972-1991.
A major part of this survey is a replication of earlier surveys. Questions about life style and decisional power at work are back again after being removed the year before. New questions deals with how much of the content the respondent reads in different papers.

Purpose:

Collect broad information about interests, purchasing habits and media choices

I mitten av 1960-talet introducerade Testologen AB, i samverkan med en grupp annonsörer, en ny undersökningsform som innebar att målgruppsdata - socio-ekonomiska data, intressen, köpvanor, innehav, köpavsikter mm - och läsvanedata insamlades i en och samma undersökning. Undersökningarna går under benämningen 'Sverige Nu', men databanken marknadsförs under benämningen ORVESTO. Namnet ORVESTO markerar målsättningen att täcka många mediagrupper: OR som i organisationspress, VE som i veckopress och STO som i storstadspress. Vid SND finns ORVESTO-undersökningar som täcker en tjuguårsperiod, 1979-1991 tillgängliga.

Syfte:

Samla in en bred information om intressen, köpvanor och mediaval

Subset of Sweden Now 1981-II, covering the period 1981-01-25 to 1981-04-03.
ORVESTO 1981-II_2
Sverige nu 1981-II
Keywords: newspaper readership; tidnings läsekrets; periodicals readership; tidskrifts läsekrets; domestic appliances; hushållsapparat; consumer goods; konsumtionsvaror; interest (cognitive processes); intresse (kognitiva processer); frequency; frekvens; Consumption and consumer behaviour; Konsumtion och konsumentbeteende; Media; Media; Public relations; Public relations; Social Sciences; Samhällsvetenskap; Media and Communication Studies; Medie- och kommunikationsvetenskap